Aplikasi Completed Feed Pellet dan Silase Rumput Untuk Kambing Boer di Sukoharjo - Joko Riyanto; Yuli Yanti; Ahmad Pramono; Ari Prasetyo (Universitas Negeri Medan, 2025)
Mertan Village, Sukoharjo has excellent potential in the livestock and agricultural sectors that support goatfarming businesses. This potential has not been utilized by farmers due to lack of knowledge and skills in feedprocessing. Providing good and appropriate feed to goats will increase livestock productivity and farmer income.Skills regarding reproduction by farmers are also still not optimal. Livestock have not been able to achieve efficientreproduction. As a solution to this problem, community service activities are carried out so that farmers can implementimproved feed management through the manufacture of complete feed and silage processing. Improvement in thereproductive aspect can be done by providing assistance to farmers on good and correct reproductive management.The methods used in this community service activity include the transfer of knowledge presented in extensionactivities in the form of: (1) introduction to types of goat feed ingredients, (2) Preparation of complete pellet feed andsilage for goats, (3) Application of feed manufacturing technology, (4) Socialization of goat livestock reproductionmanagement (5) Monitoring and assistance. The results of the activities are that farmers understand and are able toproduce quality feed and carry out reproductive improvements. The community service program that wasimplemented had a positive impact on farmers in Mertan Village, Sukoharjo. The understanding and skills of goatfarmers have increased with this activity. Farmers gain knowledge transfer in the form of types of feed ingredients,feed improvement technology, making quality feed and livestock reproduction efficiency. Farmers' participation inthis activity was very enthusiastic and responded well and received benefits from increasing the productivity of BoerGoat farming